Three-party password-based authenticated key exchange protocol based on the computational Diffie-Hellman assumption. (2018) - Sahi, Aqeel; Lai, David; Li, Yan
The three-party password-based authenticated key exchange protocol gives two clients the ability to negotiate a session key through a trusted server over a public channel. Most of the proposed 3PAKE protocols use public keys to guarantee identities; however, the sharing of public keys may lead to various types of attacks, such as a man-in-the-middle attack, which allows an attacker to simply intercept and insert traffic traversing a network. In this paper, we briefly describe an updated three-party password-based authenticated key exchange protocol and analyse its security. The proposed TPAKE protocol does not share plain-text data. Data shared between the parties are either hashed or encrypted. Using the random oracle model, the security of the proposed TPAKE protocol is formally proven under the computational Diffie-Hillman assumption. Furthermore, the analyses included in this paper show that our protocol can ensure perfect forward secrecy and can also resist many types of common attacks.